1991
DOI: 10.1002/jez.1402580114
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a role of Na+,K+‐ATPase in the hydration of Atlantic croaker and spotted seatrout oocytes during final maturation

Abstract: During final maturation the oocytes of many marine teleosts swell four to five times their original size due to uptake of water. The involvement of active inorganic ion transport and Na+,K(+)-ATPase in oocyte hydration in Atlantic croaker (Micropogonias undulatus) and spotted seatrout (Cynoscion nebulosus), marine teleosts which spawn pelagic eggs, was investigated by examining changes in the inorganic ion content of ovarian follicles containing mainly oocytes, by performing in vitro incubations of the follicl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…In various marine or brackish teleosts that spawn pelagic eggs (termed pelagophils by LaFleur and Thomas, 1991;Finn et al, 2002), an additional proteolysis of Vg-derived yolk proteins occurs during the final maturation of oocytes (FOM). It was suggested that the presence of small peptides and free amino acids (FAAs) generated during FOM-associated proteolysis of the yolk proteins contributes, at least in part, to the acquisition of an osmotic gradient necessary for uptake of water (oocyte hydration), resulting in neutrally buoyant eggs (reviews: Patiño and Sullivan, 2002;Hiramatsu et al, 2002a;Matsubara et al, 2003;Romano et al, 2004).…”
Section: Dual Vitellogenin Modelmentioning
confidence: 99%
“…In various marine or brackish teleosts that spawn pelagic eggs (termed pelagophils by LaFleur and Thomas, 1991;Finn et al, 2002), an additional proteolysis of Vg-derived yolk proteins occurs during the final maturation of oocytes (FOM). It was suggested that the presence of small peptides and free amino acids (FAAs) generated during FOM-associated proteolysis of the yolk proteins contributes, at least in part, to the acquisition of an osmotic gradient necessary for uptake of water (oocyte hydration), resulting in neutrally buoyant eggs (reviews: Patiño and Sullivan, 2002;Hiramatsu et al, 2002a;Matsubara et al, 2003;Romano et al, 2004).…”
Section: Dual Vitellogenin Modelmentioning
confidence: 99%
“…In fact, proteolytic liberation of free amino acids was reported in several species during oocyte maturation (Finn et al, 2002a;Fyhn et al, 1999). In addition, an uptake of inorganic ions also occurs during oocyte maturation (Craik and Harvey, 1987;Finn et al, 2002a;Greeley et al, 1991;LaFleur and Thomas, 1991;Wallace et al, 1992;Watanabe and Kuo, 1986). In freshwater species, changes in egg size or osmolality during maturation have been studied in several species.…”
Section: Introductionmentioning
confidence: 99%
“…Potassium ions are also essential during volume increase and water uptake of maturing oocytes although elevated levels of K are indicative of osmoregulatory failure in salmonids (Cardeilhac et al, 1979;Redding and Schreck, 1983;Bjornsson et al, 1989;Greeley et al, 1991;Liebert and Schreck, 2006). Phospholipids, inorganic phosphate and potassium are universally major components of living cells (Craik, 1982;Craik andHarvey, 1984, 1986;Lafleur and Thomas ,1991), however, in terms of their function within the chorion, this is most likely to be associated with egg hydration.…”
Section: Discussionmentioning
confidence: 99%